Analysis of Decision Number 33/Pdt.Sus-Pailit.2020/PN.Niaga Jkt.Pst Dispute between KT Corporation and PT Global Mediacom - Siregar, Hery Andi Syarif (Universitas PGRI Madiun, 2025)
Bankruptcy is a special civil law that implements Articles 1131 and 1132 of the Civil Code. Bankruptcy is a legal remedy for creditors to ask debtors to return debts. As we know, this special legal effort is an effort that can benefit creditors, but with the condition that the debt must be due and payable. The concept of a debt that has matured does not have to be in the form of a debt agreement or acknowledgment of debt. Debts that have matured can come from obligations arising from a decision such as an arbitration award between KT Corporation and PT Global Mediacom. Bankruptcy procedural law is not like ordinary civil procedural law. In bankruptcy, the principle of simple proof is adhered to. It is not like evidence in civil law in general. When the debt can be proven simply, the debtor who is applying for bankruptcy can be declared bankrupt by the Commercial Court. The problem is that a bankruptcy petition cannot always be proven simply. An example is the bankruptcy petition submitted by KT Corporation arguing that there is a legal relationship between itself and PT Global Mediacom through ICC Arbitration Decision No. 16772/CYK. However, the bankruptcy petition was rejected by the panel of judges. This makes the definition of simple evidence and debts that are due in a bankruptcy petition narrower.